Effects of exposure pathways on the accumulation and phytotoxicity of silver nanoparticles in soybean and rice. Issue 5 (28th May 2017) - Li, Cheng-Cheng; Dang, Fei; Li, Min; Zhu, Min; Zhong, Huan; Hintelmann, Holger; Zhou, Dong-Mei
Abstract: The widespread use of silver nanoparticles (AgNPs) raises concerns both about their accumulation in crops and human exposure via crop consumption. Plants take up AgNPs through their leaves and roots, but foliar uptake has been largely ignored. To better understand AgNPs–plant interactions, we compared the uptake, phytotoxicity and size distribution of AgNPs in soybean and rice following root versus foliar exposure. At similar AgNP application levels, foliar exposure led to 17–200 times more Ag bioaccumulation than root exposure. Root but not foliar exposure significantly reduced plant biomass, while root exposure increased the malondialdehyde and H2 O2 contents of leaves to a larger extent than did foliar exposure. Following either root or foliar exposure, Ag-containing NPs larger (36.0–48.9 nm) than the originally dosed NPs (17–18 nm) were detected within leaves. These particles were detected using a newly developed macerozyme R-10 tissue extraction method followed by single-particle inductively coupled plasma mass spectrometry. In response to foliar exposure, these NPs were stored in the cell wall and plamalemma of leaves. NPs were also detected in planta following Ag ion exposure, indicating their in vivo formation. Leaf-to-leaf and root-to-leaf translocation of NPs in planta was observed but the former did not alter the size distribution of the NPs. Our observations point to the possibility that fruits, seeds and other edible parts may become contaminated by translocation processes in plants exposed to AgNPs. These results are an important contribution to improve the risk assessment of NPs under environmental exposure scenarios.